Small Aromatics Bearing Two Diarylamino Termini: Highly Reducing Organic Photocatalysts - Koike, Takashi (Synlett, 2023)
Small aromatics such as anthracene, naphthalene, or benzene bearing two diarylamino termini function as highly reducing organic photocatalysts (OPCs). In particular, the small aromatic core remarkably enhances the reducing power of the catalyst in the excited state. An appropriate combination of an OPC and an electron-accepting fluoroalkylating reagent is the key to successful radical fluoroalkylation. The basic design of the photocatalyst and the photocatalytic fluoroalkylation of olefins are discussed.1 Introduction2 Basic Catalyst Design and Photo- and Electrochemical Properties3 Photocatalytic Reactions of 9,10-Bis(diphenylamino)anthracene Derivatives4 Photocatalytic Reactions of 1,4-Bis(diphenylamino)naphthalene Derivatives5 Photocatalytic Reactions of 1,4-Bis(diphenylamino)benzene6 Summary and Outlook
Keywords: photoredox catalysis; organocatalysis; radical reaction; fluoroalkylation; electron transfer; photoreaction